Project-Based Learning with Paper Quilling for Developing Fine Motor Skills in Children with Learning Difficulties: Pembelajaran Berbasis Proyek dengan Paper Quilling untuk Mengembangkan Keterampilan Motorik Halus Anak Berkesulitan Belajar - Yulianti, Lia; Chamidah, Atien Nur (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Fine motor skills are a fundamental aspect of early childhood development, requiring structured stimulation to support cognitive and physical growth. Specific background: Many teachers still rarely apply project-based learning approaches to develop fine motor skills in children with learning difficulties. Knowledge gap: Limited studies have explored the structured integration of project-based learning with paper quilling activities for this specific group. Aims: This study aimed to analyze the application of project-based learning using paper quilling media to develop fine motor skills in kindergarten children with learning difficulties. Results: Classroom action research was conducted in two cycles with three children aged 5–6. Fine motor skill achievement increased from 38%–42% (pre-cycle) to 52%–76% (Cycle I), and 82%–86% (Cycle II), meeting developmental expectations. Indicators improved in tool handling, color recognition, rolling and pasting paper, hand–eye coordination, accuracy, and independence. Novelty: This research integrates project-based learning with paper quilling for children with learning difficulties, offering a structured and engaging developmental activity. Implications: The findings provide practical strategies for educators and parents to create contextual and stimulating learning environments for fine motor development. Highlight Paper quilling activities within project-based learning improve children’s fine motor development. Structured cycles show progressive skill achievement from basic to expected levels. The approach offers practical teaching strategies for educators and parents. KeywordFine Motor Skills, Project Based Learning, Paper Quilling, Learning Difficulties, Early Childhood Education